Analisis Kepuasan Karyawan Menggunakan Metode Internal Service Quality (INTQUAL) - Irwati, Dwi; Supriyati, Supriyati; Hidayat, Ade Nurul (JURNAL TEKNIK INDUSTRI, 2021)
Employees are one of the important stakeholders in an organization. It is undeniable that the role of employees in the realization of products and services will determine the final result of a product or service. Employees in this case are defined as internal customers in the organization. If the satisfaction of employees as internal customers will certainly provide positive satisfaction to customers. Because of the importance of employee satisfaction, it is important for management to always measure and describe how the company's performance is in providing employee satisfaction. INTQUAL is a method of measuring employee satisfaction by considering employee expectations. With this method, the company will find it easier to find out the gap between expectations and actual so that it will be easier to analyze corrective actions. The results of this study, obtained 4 (four) parts of the priority scale, namely high priority, good performance, low priority and the possibility to kill / excess attributes.